Isocrates I - Isocrates (Oratory of classical Greece, 2000)
This is the fourth volume in the Oratory of Classical Greece series. Planned for publication over several years, the series will present all of the surviving speeches from the late fifth and fourth centuries B.C. in new translations prepared by classical scholars who are at the forefront of the discipline. These translations are especially designed for the needs and interests of today' undergraduates, Greekless scholars in other disciplines, and the general public. Classical oratory is an invaluable resource for the study of ancient Greek life and culture. The speeches offer evidence on Greek moral views, social and economic conditions, political and social ideology, and other aspects of Athenian culture that have been largely ignored: women and family life, slavery, and religion, to name just a few. This volume contains works from the early, middle, and late career of the Athenian rhetorician Isocrates (436-338). Among the translated works are his legal speeches, pedagogical essays, and his lengthy autobiographical defense, Antidosis . In them, he seeks to distinguish himself and his work, which he characterizes as "philosophy," from that of the sophists and other intellectuals such as Plato. Isocrates' identity as a teacher was an important mode of political activity, through which he sought to instruct his students, foreign rulers, and his fellow Athenians. He was a controversial figure who championed a role for the written word in fourth-century politics and thought